An automatic centrifugal system for rapid detection of bacteria based on immunomagnetic separation and recombinase aided amplification. Issue 19 (8th September 2022) - Wang, Siyuan; Qi, Wuzhen; Wu, Shangyi; Yuan, Jing; Duan, Hong; Li, Yanbin; Lin, Jianhan
Abstract : This study reported an automatic centrifugal system for rapid detection of foodborne pathogenic bacteria based on immunomagnetic separation (IMS) for target bacteria enrichment and recombinase aided amplification (RAA) for nucleic acid detection. Abstract : This study reported an automatic centrifugal system for rapid quantification of foodborne pathogenic bacteria based on immunomagnetic separation (IMS) for target bacteria enrichment and recombinase aided amplification (RAA) for nucleic acid detection. First, target bacteria were captured by immune magnetic nanoparticles (MNPs) to form magnetic bacteria, which were purified and enriched by magnetic separation. Then, nucleic acid extraction buffer was used to extract genomic DNA of magnetic bacteria and dissolve lyophilized RAA reagent. Finally, isothermal amplification and fluorescent detection were conducted for bacteria quantification. Bacteria magnetic separation, nucleic acid extraction and fluorescent RAA detection were elaborately achieved in a centrifugal disc with unique functional chambers and multistage siphon channels. A supporting device was developed to automatically and successively perform the programmed centrifugal protocol, including temperature control for isothermal amplification and fluorescence detection for real-time RAA analysis. Under optimal conditions, this centrifugal system enabled Salmonella detection as low as 10 CFU mL −1 in spiked chicken samples in 1 h with average recovery of 105.6% and average standard deviation of 8.4%. It has been demonstrated as an alternative for rapid detection of Salmonella .